2020
DOI: 10.1111/jre.12772
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between periodontal disease and lung cancer: A systematic review and meta‐analysis

Abstract: Periodontal disease (PD), as a chronic bacterial infection, might cause cardiovascular and some other systemic diseases, with recent studies reporting that it exhibits some connection with lung cancer. While studies have shown that poor oral health might increase the risk of lung cancer, the veracity of these reports is questionable. Therefore, this meta‐analysis was undertaken to investigate the association between PD and the risk of lung cancer. A search was run in PubMed, EMBASE, MEDLINE, CENTRAL, and Clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 66 publications
0
25
1
4
Order By: Relevance
“…In contrast to meta-analyses of observational studies suggesting that periodontal disease is associated with the risk of lung and pancreatic cancer, 68,41,42 our primary analyses did not indicate that there were significant associations between a genetic predisposition to having chronic or aggressive periodontal disease and the risk of either lung or pancreatic cancer. Given that the effect estimates for colorectal cancer and pancreatic cancer were similar but we had more colorectal cancer cases, it is possible that our pancreatic cancer analyses were underpowered.…”
Section: Discussioncontrasting
confidence: 94%
“…In contrast to meta-analyses of observational studies suggesting that periodontal disease is associated with the risk of lung and pancreatic cancer, 68,41,42 our primary analyses did not indicate that there were significant associations between a genetic predisposition to having chronic or aggressive periodontal disease and the risk of either lung or pancreatic cancer. Given that the effect estimates for colorectal cancer and pancreatic cancer were similar but we had more colorectal cancer cases, it is possible that our pancreatic cancer analyses were underpowered.…”
Section: Discussioncontrasting
confidence: 94%
“…In a meta-analysis of cohort studies [25] it was a concluded that design and quality of studies -together with the number of cases and participantssupport the association between tooth loss and both cardiovascular disease and cerebrovascular incidents. Other meta-analyses give creedence to a link between death risk [21], obesity [28], dementia [61], depression [32], Alzheimer's disease [62], asthma [63], different types of cancer [64,65] and metabolic syndrome [66] and oral health indicators. Oral diseases / infections as a risk factor for the development of various systemic conditions is a topic that has been widely investigated and debated.…”
Section: Discussionmentioning
confidence: 99%
“…A doença periodontal (DP) é caracterizada por um processo inflamatório crônico, produzido por uma complexa interação entre o estímulo patogênico (uma comunidade bacteriana) e a resposta do hospedeiro, e afeta os tecidos que circundam e sustentam os dentes (1)(2)(3). Esta patologia inclui a gengivite e a periodontite, além de ser altamente prevalente na população (4).…”
Section: Introductionunclassified